Platelets enhance lymphocyte adhesion and infiltration into arterial thrombus - Hu, Hu; Zhu, Linjing; Huang, Zhangsen; Ji, Qiushang; Chatterjee, Madhumita; Zhang, Wei; Li, Nailin (Thrombosis and Haemostasis, 2010)
Lymphocytes are present in atherosclerotic lesion. We hypothesise that platelets may facilitate lymphocyte infiltration into the arterial wall. Reconstituted human blood or whole blood was perfused through a collagen-coated parallel-plate flow chamber at different shear rates. Adhered platelets markedly enhanced lymphocyte adhesion that increased lymphocyte deposition from 10 ± 3 cells/mm2 of platelet-depleted blood to 38 ± 11 cells/mm2 of platelet-containing blood at the arterial shear rate of 500 s-1. Platelet-dependent lymphocyte adhesion was inhibited by P-selectin, CD40L, and GPIIb/IIIa-blocking agents, suggesting the involvement of multiple adhesion molecules in this heterotypic interaction. Lymphocyte deposition was more marked among T cells, and seen in both small and large cells. B and natural killer cell adhesion was, however, mainly seen in small cells. Platelet-conjugation facilitated lymphocyte adhesion, as suggested by the selective deposition of platelet-conjugated lymphocytes. In a mouse model of arterial thrombosis, FeCl3-induced thrombus formation markedly enhanced lymphocyte adhesion and infiltration into platelet thrombi, which was abolished by GPIIb/IIIa inhibition. In conclusion, platelets support lymphocyte adhesion under arterial flow conditions, which is selective among T cells and involves multiple adhesion molecules. Our data imply that platelets may facilitate the recruitment of circulating lymphocytes at the arterial injured sites.
Keywords: Platelets; lymphocytes; platelet-lymphocyte conjugates; arterial flow; thrombosis